Comparative analysis of torque-controlled IM drives with applications in electric and hybrid vehicles. - Neacsu, D.O.
This paper presents torque-controlled drives based on machine flux and torque estimation. The theoretical aspects of these methods are discussed and a comparative analysis is provided with emphasis on DSP implementation and experimental results. The problems in the application of these techniques to propulsion systems are also discussed and possible solutions are presented
Keywords: DSP implementation; PI control; Electric vehicles; Flux control loop; Fuzzy control; Hybrid vehicles; Machine flux; Propulsion systems; Rotation angle calculation; Stator voltage equation; Torque estimation; Torque-controlled IM drives; Torque-controlled drives